2015
DOI: 10.1080/02640414.2015.1085074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of swimming performance: perceptions and practices of US-based swimming coaches

Abstract: In elite swimming, a broad range of methods are used to assess performance, inform coaching practices and monitor athletic progression. The aim of this paper was to examine the performance analysis practices of swimming coaches and to explore the reasons behind the decisions that coaches take when analysing performance. Survey data were analysed from 298 Level 3 competitive swimming coaches (245 male, 53 female) based in the United States. Results were compiled to provide a generalised picture of practices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(113 citation statements)
references
References 31 publications
6
107
0
Order By: Relevance
“…13 Coaches perceive that it takes too long to carry out quantitative analysis and this outweighs any perceived advantage of conducting such work. A recent study reported that it took approximately seven and a half hours to carry out manual digitization of a relatively small amount of footage, involving ten swimmers performing three dives each.…”
Section: 69mentioning
confidence: 99%
See 4 more Smart Citations
“…13 Coaches perceive that it takes too long to carry out quantitative analysis and this outweighs any perceived advantage of conducting such work. A recent study reported that it took approximately seven and a half hours to carry out manual digitization of a relatively small amount of footage, involving ten swimmers performing three dives each.…”
Section: 69mentioning
confidence: 99%
“…A central theme of this criticism is the time required to carry out video based procedures. 13,20,89 This is certainly limiting the frequency of quantitative video analysis performed in applied settings but is likely to also decrease qualitative video practices, given that video editing for multiple swimmers can be very labour intensive in its own right. It is unsurprising therefore that much research attention is currently focused on reducing the time taken to obtain pertinent information using video and on the automation of many of the laborious manual procedures involved.…”
Section: Emerging Advances In Video Technologymentioning
confidence: 99%
See 3 more Smart Citations